Long-term impact of the SARS-CoV-2 pandemic on respiratory viruses in Germany - Eggeling, Ralf; König, Florian; Köppel, Lisa; Böhler, Laura-Inés; Böhm, Michael; Schmeißer, Norbert; Pfeifer, Nico; Kaiser, Rolf; Schnitzler, Paul (BMC public health, 2025)
Respiratory viral diseases are one of the greatest challenges facing our healthcare system, with them being one of the main causes of death. This has been demonstrated once again by the impact of the SARS-CoV-2 pandemic in recent years. We study the impact of the SARS-CoV-2 pandemic on the prevalence of respiratory viruses by analysing a subset of the Clinical Virology network database, covering 2,216,198 samples tested for 18 different viral pathogens in the time span from 2010 to 2024.